Australasian contributions to the "shell shock" literature of World War I. (August 2015) - Macleod, Sandy
Objective: Australasians contributed to the medical literature on shell shock during and after World War I. Conclusions: AW Campbell, Elliot Smith, Carmalt Jones and AG Butler made significant contributions, and several 'frontline doctors' recorded astute observations.